Immunological diagnosis of nasopharyngeal carcinoma (NPC) by immunoperoxidase assay (IPA) method using and- VCA-EBV IgA - Indrayani Purba Indrayani Purba (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1997)
Nasopharyngeal Carcinomas (NPC) are the most frequent malignancy cases found at Ear, Nose and Throat (ENT) Department. Patients are commonly admitted in a severe condition. The success of therapy depends on the early detection of the disease. The most frequently NPC is WHO III type. WHO II and III types have close relationship to EBV. One of the methods to detect an early stage of the disease is by sero-immunology examination for anti VCA-EBV-IgA (VCA-IgA) using IPA method. The results of this VCA-IgA examination in this study were compared to the clinical examinations of NPC and biopsies to observe an analytical performance in terms of reproducibility, diagnostic performance and comparison test (significance and correlation tests). The VCA-IgA examination has been performed at the Department of Clinical Pathology, Dr. Sardjito General Hospital on 30 patients with clinical examination of NPC confirmed by biopsy, 30 normal subjects, 10 suspected KP patients, and 10 patients with positive ASTO. The results of this examination indicated that the reproducibility of VCA-IgA examination by IPA method is very good (Kappa = 81%). For diagnostic performance, a high sensitivity result is obtained (96%). There is no significant difference between the result of VCA-IgA examination with IPA method and NPC with clinical examination & biopsy (p > 0,05). It can be concluded that IgA anti VCA-EBV examination IPA method is useful in the early NPC diagnosis.Key Word : nasopharyngeal carsinoma - IgA anti VCA-EBV - immunoperoxidaseassay - analytic & diagnostic performance - reproducibility